La Relación Teoría–Práctica en la Formación del Trabajador Social: Sistematización de Experiencias en un Contexto de Salud - Gicela Carola Aguilar Mora; Nicolas Jhon Ponce Jaramillo (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
This work systematizes the pre-professional practicum experience carried out by a student of the Social Work Program at the Universidad Técnica de Machala. The practical setting was assigned through the Social Work in Companies course, leading to a placement in a health care unit, whose institutional identity is kept confidential for ethical reasons. The objective is to critically analyze the relationship between theoretical training and its application within a highly complex health context. The experience took place over 96 hours, allowing for the reconstruction of the lived process and reflection on the institutional, professional, and educational dynamics involved. It is developed from a qualitative, critical-reflective approach, supported by the methodology of systematization of experiences. For the reconstruction and analysis of the experience, techniques such as a field diary, reconstruction matrix, timeline, and critical questions were used, facilitating a critical and reflective stance. The results show that the experience in the health care unit generated a contrast between what was learned in academia and the real demands of the health field. The pre-professional practicum allowed for the progressive development of professional competencies related to assertive communication, mediation, and social management.